What Are the Standards of Excellence for Theological Interpretation of Scripture? - East, Brad (Journal of theological interpretation, 2020)
The canon of Holy Scripture is unique, given its nature and ends in the economy of grace and the mission of the church. Its reading must accordingly be unique, though not wholly dissimilar to ordinary practices of reading. This article advances a proposal for the standards of excellence proper to specifically theological interpretation of Scripture. That is, it seeks to answer the question, "What makes a theological reading of the Bible good?" Following an overview of the theological and ecclesial status of Scripture and its reception, the article offers two sets of standards for excellent theological interpretation. The first is theological, measuring the proposed reading by its relation to the triune God’s purposes for Scripture in the life of the church. The second is hermeneutical, judging the proposed reading by specifically literary or textual criteria. These latter overlap with more common scholarly practices of reading, though they remain distinctively Christian; their secondary status, moreover, emphasizes the difference made by Scripture’s character as God’s word and the church’s book.